The Role of Oc Eo Ancient City in The International Maritime Trade Network (From The First to The Seventh Century) - Thang, Dang Van; Tuyet , Vo Thi Anh; Nhu, Vo Thi Huynh; Hop, Dao Vinh (Journal of Ecohumanism, 2025)
Oc Eo (Vietnamese: Óc Eo) is an archaeological site in the Mekong Delta, located in southern Vietnam (Óc Eo commune,Thoại Sơn district, An Giang province). Oc Eo is often mentioned in research about ancient Southeast Asia as a part of the Funan kingdom. Some studies have identified Oc Eo's role as a trade, political, and religious center of Funan, but the position of Oc Eo in ancient international maritime trade network has not been clearly stated. Approach this issue from archaeology perspective, the authors surveyed the sites and studied artifacts found at sites in the Oc Eo area, particularly origin of these artifact. Ancient Chinese bibliographies are also cited to supplement the article. The findings state the favorable conditions for the development of Oc Eo as a port city: the location of a traffic hub of inland canals; a stop on the sea route from east to west; and having sources of local products that can be used as goods to exchange with merchants. The article also proves that Oc Eo city was an important port in the maritime trading system in ancient Southeast Asia during the period from the first to the seventh century CE. which was a transit point connecting between China and Southeast Asia, China, and India, maybe even the Mediterranean.